PENGEMBANGAN MARKETPLACE LOKAL SEBAGAI STRATEGI PENINGKATAN PENDAPATAN PELAKU UMKM - Syarifuddin; Indah Sulistiani, Ratna Jaya; Al-Amin (JOURNAL OF COMMUNITY DEDICATION, 2025)
The purpose of this research is to see how Local Marketplace Development is a Strategy for Increasing Income of MSME Actors. The method of this research is This research is a type of literature research; This means that the information materials used come from library sources in the form of books, encyclopedias, magazines, journals, newspapers, journals, and others. The form of this research is descriptive, analytical, and critical. Therefore, the author can comprehensively describe how Local Marketplace Development is a Strategy for Increasing Income of MSME Actors. The results of this research are Digitalization and E-Commerce, Increasing visibility in the digital market is an effective way to reach more consumers and expand the market. E- commerce platforms allow MSME actors to sell their products in various regions, even internationally.